2010
DOI: 10.1016/j.proeng.2010.09.051
|View full text |Cite
|
Sign up to set email alerts
|

A complete low voltage analog lock-in amplifier to recover sensor signals buried in noise for embedded applications

Abstract: This paper presents a low-voltage 3V single supply analog lock-in amplifier (LIA) for processing small AC sensor signals buried in noise, including those presenting a relative phase with respect to the reference signal. Reference and bias sensor signals are provided by a quadrature oscillator. Experimental results confirm the capability of the proposed lock-in amplifier to effectively recover information from signal to noise ratios below 0.025, with an error below 9%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Actually it is also a kind of correlation detection. Figure.1 Lock-in amplifier experimental block diagram Gabal et al [8] studied the small AC sensor signals which were buried in noise. They thought that using low voltage simulated phase-locked amplifier to detect sensor signals with low SNR is very effective.…”
Section: (4) Lock-in Amplifiermentioning
confidence: 99%
“…Actually it is also a kind of correlation detection. Figure.1 Lock-in amplifier experimental block diagram Gabal et al [8] studied the small AC sensor signals which were buried in noise. They thought that using low voltage simulated phase-locked amplifier to detect sensor signals with low SNR is very effective.…”
Section: (4) Lock-in Amplifiermentioning
confidence: 99%
“…Before, most large-scale ERT surveys used either high-frequency single-channel seismic dataloggers (e.g. Reftek Texan-125) or three-channel magnetotelluric dataloggers (Roßberg, 2007;Golden et al, 2004). However, the latter provided only a maximum sampling frequency of 8 Hz leading to anthropogenic noise energy folding into the signal frequency band (typically slightly below 1 Hz) due to aliasing effects.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, performances at low frequencies are significantly better. The field of applications which require the detection of very low signals in noisy surroundings where the use of lock-in detectors from optics is widespread (Andersson et al, 2007;Masciotti et al, 2008;Holzman et al, 2005), impedance spectroscopy (Albertini and Kleemann, 1997), wireless networks (Gabal et al, 2010), biologic applications (Ferri et al, 2001;Johnson et al, 2002), electron spin resonance (ESR) (Vistnes et al, 1984;Murányi et al, 2004) to nuclear magnetic resonance (NMR) (Saam and Conradi, 1998;Caracappa and Thorn, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the synchronous detection architecture much care needs to be taken for perfect matching of the frequency and phase values of the data with the reference signal, otherwise, the signal cannot be completely recovered. Gabal et al has shown the use of two parallel PSD to eliminate system phase dependence (Gabal et al 2010). Recently, Marcellis et al presented a LIA chip that performs automatic alignment of the relative phase between the input and the reference signal and performs self-tuning (De Marcellis et al 2013).…”
Section: Introductionmentioning
confidence: 99%